Does Formalization of Informal Enterprises Matter? Evidence from Rwanda - Faustin Maniraguha (RIRAI Publisher, 2020)
In this decade, the formalization of informal sector is challenging as it provides jobs to the big number of the population and on the other hand, this group of active population work in conditions, which do not allow them to benefit some advantages from the government and these lead to not providing enough contribution to the economic growth. The main objective of the study was to find out the factors underlying for formalization of informal enterprises in Rwanda. In order to respond to the main objective, we used a desk research approach and we found that there is a necessity of enterprise formalization in Rwanda and the identified key factors are the enterprise motives/long term objectives, cash less economy/innovation in payment system and government policy for enterprise registration. The study also illustrated the factors or ways for private informal-rural enterprise formalization process may consider and some of them are affordable cost of taxation, accessibility to finance, accessibility to the markets as well as the time taken for getting legal documents. From the findings, the study recommend that the consistency capacity building so that to help managers to understand the necessity of informal sector formalization, government to continue working on the minimization of the costs related to the enterprise registration that include time, distance and other procedures and government also to continue enhancing infrastructures in rural zones. The study used secondary data both qualitative and quantitative from existing reports and data from National Institute of statistics of Rwanda.